2020
DOI: 10.1103/physrevlett.124.113003
|View full text |Cite
|
Sign up to set email alerts
|

Production of HD Molecules in Definite Hyperfine Substates

Abstract: Polarized atomic beam sources have been in operation since many years to produce either nuclear polarized atomic hydrogen or deuterium beams. In recent experiments such a source was used to polarize both isotopes independently at the same time. By recombination of the atoms, HD molecules with all possible nuclear spin combinations can be created. Those spin isomers are useful for further applications like precision spectroscopy, as polarized targets for laser-particle acceleration, polarized fuel for fusion re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Powering the magnet at its maximum allowed current (180 A), we measured 1.2 T in the middle of the poles. The required magnetic field for fusion application is in the range of 1 T, which matches exactly with the system used to produce hyper-polarized molecules as fusion fuel from the recombination of a polarized atomic beam [6].…”
Section: Materials and Equipmentmentioning
confidence: 80%
See 2 more Smart Citations
“…Powering the magnet at its maximum allowed current (180 A), we measured 1.2 T in the middle of the poles. The required magnetic field for fusion application is in the range of 1 T, which matches exactly with the system used to produce hyper-polarized molecules as fusion fuel from the recombination of a polarized atomic beam [6].…”
Section: Materials and Equipmentmentioning
confidence: 80%
“…We exploited the opportunity to upgrade our system to host a new coldhead (RDK-415D from SHI Cryogenics Group), available from our collaborators [6], with a nominal temperature of 40 K and a cooling power in the range of 42 W on the first stage and 4 K and 1.8 W on the second stage.…”
Section: Details On Solutions Adopted In the Upgraded Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This would require less of a construction project, mainly adapting existing equipment, but would involve many more stages and would become more of a labor effort. (There are also Stern-Gerlach based molecular-beam methods of producing polarized D 2 that could in principle be utilized [70,71], at least for a polarization survival test. However, since their fluxes are rather low, material would have to be collected over some time period without losing significant polarization, and a method would need to be developed to encapsulate the resulting polarized D 2 for injection.…”
Section: Polarized D Pellet Fuelingmentioning
confidence: 99%
“…In past experiments polarization measurements with a Lamb-shift Polarimeter (LSP) were typically performed with protons or deuterons. In more recent projects it was shown that the polarization measurement of 𝐻 + 2 , 𝐷 + 2 and 𝐻𝐷 + molecular ions is possible as well [1,2]. Furthermore, there exists a debate about the possibility to measure the polarization of 𝐻 − ions directly with a LSP.…”
Section: Introductionmentioning
confidence: 99%